A new genus and species of gekkonid lizard (Squamata: Gekkota: Gekkonidae) from Hormozgan Province with a revised key to gekkonid genera of Iran - Safaei-Mahroo, Barbod; Ghaffari, Hanyeh; Anderson, Steven C. (Zootaxa, 2016)
We describe a new genus and species of gekkonid from two gravid specimens which were found within Koh-e Homag Protected Area, Hormozgan Province, southern Iran. The genus Parsigecko gen. nov. can be distinguished from other genera of Middle East Gekkonidae by a combination of the following characteristics: digits not dilated, dorsal tail covered with small scales without any tubercles or keels, having two strong keeled and pointed scales on each side of each annulus. Parsigecko ziaiei sp. nov. is a ground-dwelling lizard. The new species was found in the Zagros Mountain forest steppe patch with scattered wild pistachio trees and mountain almond shrubs surrounded by South Iran Nubo-Sindian desert and semi-desert habitat in the south of Iran. The genus is the 13th gekkonid genus known from Iran, and the only gekkonid genus endemic to the Zagros Mountains. A key to the genera of the Gekkonidae in Iran is provided.